Heuristic and genetic algorithms for solving minimum-energy multicasting problem in duty-cycled wireless sensor networks - Dương, Nguyễn Thái; Bình, Huỳnh Thị Thanh; Sơn, Ngô Hồng (Journal of Computer Science and Cybernetics, 2014)
We study the Minimum-Energy Multicasting problem in Duty-Cycled-Wireless Sensor Networks (DC-WSN). In DC-WSN, nodes can switch between active and dormant states to save energy. This problem has  proved to be NP-hard. This paper proposes a heuristic algorithm and a genetic algorithm for solving this problem. We compare the proposed algorithms with TCS - the best known algorithm - by mean of simulation on four typical WSN topologies. Experimental results show that our algorithms significantly outperform TCS in terms of minimizing the energy cost.